2015
DOI: 10.1007/s11427-015-4958-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of TRPP2 in agonist-induced gallbladder smooth muscle contraction

Abstract: TRPP2 channel protein belongs to the superfamily of transient receptor potential (TRP) channels and is widely expressed in various tissues, including smooth muscle in digestive gut. Accumulating evidence has demonstrated that TRPP2 can mediate Ca(2+) release from Ca(2+) stores. However, the functional role of TRPP2 in gallbladder smooth muscle contraction still remains unclear. In this study, we used Ca(2+) imaging and tension measurements to test agonist-induced intracellular Ca(2+) concentration increase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The results are expressed as the mean cell count of the four fields. ] i was measured using methods described elsewhere [13]. Briefly, the seeded Hep2 cells were loaded with 10 μmol/L Fluo-8 (Invitrogen, USA) with 0.02% pluronic acid F-127 (Sigma-Aldrich Co., USA) at 37 °C for 30 min.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The results are expressed as the mean cell count of the four fields. ] i was measured using methods described elsewhere [13]. Briefly, the seeded Hep2 cells were loaded with 10 μmol/L Fluo-8 (Invitrogen, USA) with 0.02% pluronic acid F-127 (Sigma-Aldrich Co., USA) at 37 °C for 30 min.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
“…However, the TRPP2 and PKD1 complex can exert its effect on the kidney epithelium in the pathway that controls epithelial proliferation, differentiation and apoptosis via regulating intracellular Ca 2+ [7]. TRPP2 is not only identified as a likely mutant target responsible for autosomal dominant polycystic kidney disease (ADPKD), but also widely expressed in various cells and participates in many activities relating to proliferation and differentiation, such as those involved in Alzheimer's disease, myocardial hypertrophy, arterial hypertension, and tumour formation [5,[8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The transient receptor potential polycystic 2 (TRPP2, also known as polycystin-2, PC2, or PKD2) is a pivotal member of the mammalian transient receptor potential superfamily of channel proteins (5,27). TRPP2 is widely expressed in various tissues, including several types of smooth muscle cells, such as those in cerebral arteries, mesenteric arteries, the aorta, the gallbladder, and airway (6,7,22,24,29,34). The TRPP2 protein forms six transmembrane segments with an endoplasmic reticulum (ER) retention signal in the COOH-terminal domain and interacts with numerous proteins, mainly including cytoskeletal components (7,19).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that TRPP2 channels are widely distributed in the plasma membrane and endoplasmic reticulum (ER) ( Tsiokas, 2009 ). Xingguo et al found that knockdown of TRPP2 protein in GBSM of guinea pigs significantly decreased Ca 2+ release and extracellular Ca 2+ influx evoked by carnosine (CCh), thereby inhibiting endothelin-1 (ET-1) and cholecystokinin-induced gallbladder contraction ( Zhong et al, 2016 ). Cholecystokinin (CCK) and ET-1 receptors play an important role in GBSM contraction.…”
Section: Trp Channels In the Gallbladdermentioning
confidence: 99%